Alisol A 24-Acetate and Alisol B 23-Acetate Induced Autophagy Mediates Apoptosis and Nephrotoxicity in Human Renal Proximal Tubular Cells - Wang, Chunfei; Feng, Liang; Ma, Liang; Chen, Haifeng; Tan, Xiaobin; Hou, Xuefeng; Song, Jie; Cui, Li; Liu, Dan; Chen, Juan; Yang, Nan; Wang, Jing; et al. (Frontiers in Pharmacology, 2017)
In the present study, we explored whether alisol A 24-acetate (24A) and alisol B 23-acetate (23B) induced autophagy accompanied with apoptosis and nephrotoxicity via PI3K/Akt/mTOR signaling pathway in HK-2 cells. Importantly, the protein expression and mRNA level of Clusterin, Kim-1 and TFF-3 could be significantly increased by 23B (15 μM) and 24A (6 μM), which was a speculation of nephrotoxicity connected with HE staining of rat kidneys. The results showed that autophagy could be induced by both 23B and 24A in HK-2 cells via significantly enhancing the ratio of LC3II/LC3I, the protein expression of Beclin-1 as well as the mRNA level of LC3 and Beclin-1. Furthermore, cell apoptosis could be triggered by 23B and 24A via significantly decreasing the protein expression and mRNA level of Bcl-2 and Bcl-xl. An autophagy inhibitor, 3-methyladenine, could partially reverse cell viability and conversely change the ratio of LC3II/LC3I and the protein expression of Bcl-2 and Kim-1. Meanwhile, PI3K/Akt/mTOR signaling pathway could be inhibited by 23B and 24A. Thus this study helped to understand that 23B and 24A induced autophagy possibly resulted in apoptosis and nephrotoxicity through PI3K/Akt/mTOR signaling pathway and would facilitate further studies for Rhizoma alismatis nephrotoxicity.